2020
DOI: 10.1097/prs.0000000000007065
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Evaluating Speech Outcomes in Classic versus Occult Submucous Cleft Palate Using a Primary Furlow Palatoplasty Technique

Abstract: Background: No consensus exists on the selection of procedures for the treatment of submucous cleft palate, with scarce reports on long-term outcomes from single-surgeon experience. This study assessed the outcomes of using extended indication criteria of Furlow palatoplasty as the first-line procedure for the management of submucous cleft palate–associated velopharyngeal insufficiency. Methods: Consecutive nonsyndromic patients with submucous cleft pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 54 publications
4
20
0
Order By: Relevance
“…Its management remains challenging. 4,27 To describe the speech and velopharyngeal function of children with SMCP treated at our institution, we analyzed various variables.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Its management remains challenging. 4,27 To describe the speech and velopharyngeal function of children with SMCP treated at our institution, we analyzed various variables.…”
Section: Discussionmentioning
confidence: 99%
“…This intraoral examination could be with or without nasopharyngoscopic evaluation as an additional diagnostic method to evaluate the structure (anatomy) of the velopharyngeal valve when there were vague clinical findings in symptomatic children older than 4 years (that is to say, collaborative patients). 27 In most cases, our team uses nasopharyngoscopic examination to confirm the suspicion of occult SMCP, after VPI diagnosis, even if there is no finding on intraoral inspection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Indeed, the choice of surgical treatment often varies depending on global location. Furlow's palatoplasty has been shown to provide satisfactory postoperative speech with a low complication rate 22,23 and safe use demonstrated in both overt and occult SMCP. 24 A systematic review comparing speech outcomes of SMCP with Furlow palatoplasty and pharyngeal flap combined with intravelar veloplasty confirmed the efficacy of both repair options though concluded that pharyngeal flaps should be considered in those with significant hypernasality.…”
Section: Discussionmentioning
confidence: 99%